Utility of repeated antinuclear antibody tests: a retrospective database study. (July 2020) - Yeo, Ai Li; Le, Suong; Ong, Jason; Connelly, Kathryn; Ojaimi, Samar; Nim, Hieu; Morand, Eric F; Leech, Michelle
Summary: Background: Anti-nuclear antibody (ANA) testing is frequently used as a diagnostic or screening test in patients with inflammatory or musculoskeletal symptoms. The value of repeat testing is unclear. We sought to evaluate the frequency, utility, and cost of repeat ANA testing. The main objective was to assess the positive predictive value of a repeat ANA test for the diagnosis of rheumatological conditions associated with ANA. Methods: In this retrospective cohort study, we analysed data from a single, multisite tertiary health network in Australia across a 7-year period. ANA and other autoimmune test results were obtained from the hospital pathology system with a positive ANA titre cutoff set at 1:160. Clinical information was sourced from clinical information systems on any patient who had a change in ANA result from negative to positive on repeat testing. The cost of repeated ANA testing was calculated using the Australian Government Medicare Benefits Schedule. Findings: From March 19, 2011, to July 23, 2018, a total of 36 715 ANA tests were done in 28 840 patients at a total cost of US675 029 (2018 equivalent). 14 058 (38·3%) of these ANA tests were positive. 7875 (21·4%) of the ordered tests were repeats in 4887 (16·9%) of the patients, among whom 2683 (54·9%) had initially negative tests, and 2204 (45·1%) had initially positive tests. 511 (19·0%) of the 2683 patients with initially negative tests had a positive result on at least one repeat test, with a median time to first positive result of 1·74 years (IQR 0·54–3·60). A change from negative to positive ANA was associated with a new diagnosis in only five (1·1%) of the 451 patients with clinical information available and no previous diagnosis of an ANA-associated rheumatological condition, yielding a positive predictive value of 1·1% (95% CI 0·4–2·7). Interpretation: Repeat ANA testing after a negative result has low utility and results in high cost. Funding: Monash Health.